Dry Rendering Methods and Quality Attributes of Chicken Skin Oil - Aulia, Hasna Rahma; Budi, Faleh Setia; Indrasti, Dias (Jurnal Ilmu-Ilmu Peternakan, 2026)
Chicken skin, as a byproduct, can cause environmental impacts if poorly managed, even though it also has potential as a food product. Diversification of chicken skin derivatives is necessary because these materials are susceptible to spoilage from microbial activity. In recent years, chicken skin oil has been widely used in households as a cooking fat to enhance flavour and aroma. However, research on methods for producing high-quality chicken skin oil remains limited. The purpose of this study was to evaluate the effects of different rendering methods on oil yield, peroxide value, acid value, and moisture content and determine the best method on the basis of these parameters. Chicken skin was rendered using pan, oven, and microwave rendering methods, and the extracted oils were characterized using standardized analytical methods. The results of the statistical analysis indicated that compared with the other methods, microwave rendering resulted in the highest yield (21.09%) and a significantly lower peroxide value (2.18 meq O?/kg). Oven rendering demonstrated oxidative stability comparable to that of microwave rendering, despite a lower yield (13.31%). The acid value and moisture content of the various rendering techniques did not differ significantly. Microwave rendering was found to be the best dry rendering technique by the De Garmo effectiveness index, which balanced oxidative stability and yield. These results support the wider use of poultry byproducts in food applications by demonstrating that microwave rendering is an effective and promising technique for producing chicken skin oil with desired physicochemical properties.